2006
DOI: 10.21101/cejph.a3398
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemic of Obesity in Children and Adolescents in the World

Abstract: The prevalence of obesity has reached alarming levels, affecting virtually both developed and developing countries of all socioeconomic groups, irrespective of age, sex or ethnicity. Concerning childhood obesity, it has been estimated that worldwide over 22 million children under the age of 5 are severely overweight, and one in 10 children are overweight. This global average reflects a wide range of prevalence levels, with the prevalence of overweight in Africa and Asia averaging well below 10% and in the Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
213
1
33

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(251 citation statements)
references
References 37 publications
(72 reference statements)
4
213
1
33
Order By: Relevance
“…The overweight rates in the Brazilian population have increased to the point of being considered an epidemic 2,22 . Along with a decline in child malnutrition, Brazil has seen a 16.7% increase in child overweight 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The overweight rates in the Brazilian population have increased to the point of being considered an epidemic 2,22 . Along with a decline in child malnutrition, Brazil has seen a 16.7% increase in child overweight 3 .…”
Section: Discussionmentioning
confidence: 99%
“…7,42 In general, the prevalence and trends of childhood overweight are known to be similar in the Americas and Europe. 3,43 Unfortunately, our cross-sectional data do not allow the identification of target groups for obesity-prevention programs because the examined percentiles refer to the outcome variable BMI-SDS at preschool age. On the basis of these data, it is unclear whether overweight children at school entry would also have been overweight at an earlier age, when a potential intervention (such as breastfeeding) might take place.…”
Section: Discussionmentioning
confidence: 99%
“…The global epidemic of childhood obesity has become a serious public health concern [1], and recent studies suggest that the prevalence of non-alcoholic fatty liver disease (NAFLD) is increasing in children [2,3], especially in obese children [4,5]. This condition is considered to be the most common form of chronic liver disease in the pediatric population [6].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the study reported here was: (1) to determine whether each component of metabolic syndrome is positively correlated with the degree of NAFLD (doseresponse relationship); (2) to determine whether pediatric NAFLD is closely related to metabolic syndrome, insulin resistance, and waist circumference (WC).…”
Section: Introductionmentioning
confidence: 99%